The Role of Chemical Treatments on Curaua Fibers on Mechanical and Thermal Behavior of Biodegradable Composites - Janaíne M. de Oliveira; Vitor M. Z. Sousa; Linconl A. Teixeira; Rosineide M. Leão; Rita C. M. Sales-Contini; Volker F. Steier; Sandra M. da Luz (Applied Sciences)
Biodegradable composites combining thermoplastic polymers and natural fibers could originate materials with synergetic mechanical and thermal properties, keeping their biodegradability. This paper describes biodegradable polymers’ mechanical and thermal properties, such as polylactic acid (PLA) and polyhydroxybutyrate (PHB) reinforced with curaua fibers. To improve the interface between matrix and reinforcement, the curaua fibers were treated by two routes: (1) treatment with hot water and subsequent mercerization with NaOH; (2) treatment with chlorite and subsequent mercerization with NaOH. The composites of PLA and PHB reinforced with natural or modified fibers (10 and 20 wt%) were obtained by extrusion and injection molding. The influence of fiber content and treatment on composite properties was studied by tensile and flexural tests, scanning electron microscopy (SEM), X-ray diffraction (XRD), thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC). The results showed the removal of hemicellulose and lignin from the fibers, increasing their crystallinity and slightly decreasing their thermal stability after chemical treatments. Also, the DSC technique showed that the insertion of the curaua fibers increased the crystallinity index of all composites/PLA. The mercerized-curaua (20 wt%)/PLA composite showed the best result in the mechanical behavior, both in tensile and bending tests. The PHB composite, reinforced with curaua fibers and treated with hot water and mercerization (20 wt%), showed the best result regarding mechanic performance. To conclude, all composites improved mechanical properties compared to pure polymers.